(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the recent year, greater stress has been laid on the quality rather than the quantity of training. The coaches and teachers of Physical Education want their sportsman to extract maximum achievement from their training procedures without causing too much strain on them. This is Possible only if coaches and teachers of physical education apply the most beneficial means of training in the most economical manner for enhancing the performance of their athletes. The present study was conducted on 5 male University level sprinters in the age group of 19 to 23 years. All the 5 sprinters were tested on varied block spacing in Crouch start on acceleration speed 10m, 20m, 30m and 40 meters. The distances 10m, 20m, 30m and 40 meters were used from different blocks spacing such as bunch, medium and elongated. The subjects were allowed to take 3 trials on each block spacing and best time on each block spacing was considered for the analysis of data. The purpose of the study was to determine comparative effects on varied Blocks Spring in crouch start on acceleration speed.